The relationship between the time factor and in-hospital mortality in the hospitalized patients - Eryiğit, Veysi; Yüksel, Melih; Erimşah, Mehmet Emre; Karaaslan, Ulaş (The European Research Journal, 2022)
Objectives: As in-hospital deaths are encountered by all healthcare professionals, investigating the factors affecting in-hospital mortality may help to reduce the number of deaths. In this study; the relationship between time factor and in-hospital deaths is examined. Methods: The study included all hospitalized patients who died at Balikesir State Hospital between January 01, 2014 and December 31, 2014. Time of death, workdays, and holidays were examined on a monthly and seasonal basis and at shift change times. In calculating in-hospital mortality, ’Crude Death Rate (CDR)’ was used. Results: The number of in-hospital deaths during the study period was found to be 1418. It was discovered that the number of patients hospitalized per day was 314.6 ± 46.95, the number of hospitalized patients who died per day was 3.88 ± 2.16, and the mean daily CDR was 12.77 ± 7.5. Additionally, CDR was found to be as 7.56 ± 5.5 in males, while it was 5.21 ± 4.55 in females. Moreover, CDR was 13.07 ± 7.52 on workdays, whereas it was 12.07 ± 7.43 on holidays. As for seasons, CDR was found to be as 14.35 ±8.63 in summer, while it was 11.43 ± 7.84 in winter. Conclusions: In-hospital mortality, the death rate of males was higher than females while their average age was found to be less than females. No change was observed at shift change hours. The mortality rate increased in summer. However, no difference was found between workdays and holidays in terms of mortality rate.